Experimental and Theoretical Characterization of the Release Kinetic of Carvacrol as Inclusion Complexes with β-cyclodextrin in Poly(Lactic Acid) and Mater-Bi® Processed by Supercritical Impregnation - Rodriguez-Mercado, F; Romero-Figueroa, J; Quijada-Maldonado, E; Torres-Mediano, A; Olea-Chandia, F; Rivera-Fuentealba, P (Elsevier B.V., 2024)
The incorporation of active compounds into polymeric matrices using traditional methods has several drawbacks mainly due to the high volatility and thermal sensitivity of these substances. A solution to this problem could be the incorporation of bioactive compounds forming inclusion complexes as a strategy to improve the chemical stability, bioactivity and achieve controlled release. In this work, β-cyclodextrin/carvacrol inclusion complex was prepared by spray drying to be incorporated into poly(lactic acid) (PLA) and Mater-Bi® films by supercritical CO2 impregnation. The impregnation process was carried out at pressures of 10, 15 and 20 MPa and at 40 °C. Both polymers showed the highest amount of incorporated inclusion complex at 15 MPa, where the percentage of impregnation varied from 0.6 % to 7.1 % in Mater-Bi® and PLA, respectively. Release tests for PLA films impregnated with inclusion complex showed a slow release of the active compound, which did not reach equilibrium after 350 h under the experimental conditions. This prolonged release was not observed in Mater-Bi® due to the lower incorporation of the inclusion complex. The release rate was described herein by a comprehensive phenomenological model considering the decomplexation kinetics combined with the equilibrium and mass transfer expressions. © 2024